Survival and handicap of infants with spina bifida. Issue 11 (November 1980) - Althouse, R; Wald, N
Abstract : A follow-up study was carried out on 213 infants born with spina bifida cystica (including encephalocele and occipital meningocele) from 1965 to 1972 to women resident in Oxfordshire and the western part of Berkshire. The 5-year survival rate was 36% (39/107) for those with open lesions, 60% (30/50) for those with closed ones, and 18% (10/56) for those with lesions which could not be classified (not known) but which were probably nearly all open. The extent of handicap among these survivors was assessed by means of criteria described by Lorber; among those with open lesions (including 'not known') 84% (41/49) were severely handicapped, 10% (4/49) were moderately handicapped, and only 6% (3/49) had no handicap; among those with closed lesions, 37% (11/30) were severely handicapped, 33% (10/30) were moderately handicapped, and the remaining 30% (9/30) were not handicapped. Closed head lesions (encephalocele or occipital meningocele) were more often associated with severe handicap (6/8; 75%) than were closed spinal lesions (5/22; 23%). The children with open lesions who survived for at least 5 years spent, on average, at least 6 months in hospital during the first 5 years of their life and had, on average, at least 6 major surgical operations. In comparison, those with closed lesions spent one-third less time in hospital, and had fewer than half as many operations. During the period of the study a selective treatment policy was adopted typical of that commonly practised now, and all the infants were born before antenatal screening had been introduced. Our results therefore may be helpful in assessing the benefits to be expected from antenatal screening for open spina bifida.